Populist Party Responsiveness and Populist Party Voter Satisfaction With Democracy in Europe - Brause, Simon D. (2024)
Voters of populist parties tend to be dissatisfied with democracy. Some scholars attribute this dissatisfaction with how our democracies function to poor representation by mainstream parties and a feeling of not being heard. We should see this representation improve with the success of populist parties. This improved representation should, in turn, have a positive impact on populist party voters’ satisfaction with democracy (SWD). Existing case studies have only looked at the link between formal populist party representation in parliament or government, and populist party voters’ SWD, with mixed findings, the most puzzling of which is that populist party voters may even become less satisfied with growing formal representation. There is no comparative study on populist parties’ actual responsiveness to populist party voters and the connection to their SWD. Thus, we ask: How well do populist parties represent populist party voters, and how does this populist party responsiveness influence populist party voters’ satisfaction with democracy? We define populist party responsiveness as issue-based agenda-responsiveness between populist party voters and populist parties and investigate the link to SWD using data on 21 countries from the 2019 European Election Studies. We find that populist parties in Europe are not generally more responsive to populist party voters than mainstream parties. Populist parties’ agenda-responsiveness has a positive effect on populist voters’ SWD while being in government does not increase the positive effect of populist party responsiveness on their voters’ SWD. They may be disenchanted by how well their parties can eventually “walk the talk.”